The Role of Pancasila Education and Citizenship Subject Teachers in Strengthening Pancasila Democratic Values for High School Students - Rahima, Najwa (Educational Insights, 2024)
The subject of Pancasila and Civic Education (PPKn) is the most strategic subject to strengthen students' democratic attitudes because it is closely related to habits or customs that need to be improved in everyday life so that it is easier to practice. The role of Civics teachers is needed to direct students to get maximum teaching and be able to practice democratic values. This article aims to find out the meaning of Pancasila and Citizenship Education, Pancasila democracy, and analyze the role of teachers in strengthening democratic values in high school students. The literature study method with a literature review approach was applied by the author in preparing the article. Data collection techniques use documentation studies by collecting documents that are in accordance with the research topic. The results of the study explained that Pancasila and Citizenship Education is a subject that is closely related to lessons that relate to human relations in a country, whether social, economic, or political relations. Pancasila democracy is a system of government that is run in Indonesia based on the values contained in Pancasila itself. The results of the analysis of the role of Civics teachers in high school students show that the role of educators is very important to apply and implement democratic values for students. The implementation is shown by several democratic attitudes such as freedom of opinion, respect for other people's opinions, deliberation to reach consensus, accustoming students to participate in elections within the school, and so on. Strengthening democratic values is very important to teach because students are part of society who will later play a role in monitoring democracy in Indonesia.